Amelioration of H4[W12SiO40] by nanomagnetic heterogenization: For the synthesis of 1H–pyrazolo[1, 2‐b]phthalazinedione derivatives. (15th September 2017) - Arora, Priya; Rajput, Jaspreet Kaur
Abstract : We conveniently coated silicotungstic acid (STA, H4 [W12 SiO40 ]) on amino‐functionalized Si–magnetite nanoparticles, as surface functionalization of magnetic nanoparticles is an excellent way for green and efficient catalysis. The nanoparticles were structurally characterized using various techniques. The catalytic activity and recyclability of the STA–amine–Si–magnetite nanoparticles were probed through synthesis of 1 H –pyrazolo[1, 2‐ b ]phthalazinedione derivatives. The reaction proceeds smoothly to provide products in excellent yields and short reaction times. The catalyst could be readily recovered using a simple external magnet and reused several times without any significant loss in activity. Herein, we report a comparison of the activity of H4 [W12 SiO40 ] as a homogeneous and heterogeneous catalyst, the latter being found to be more efficient. The findings offer effective methods for environmentally friendly synthesis of pyrazolo[1, 2‐ b ]phthalazinedione derivatives. Abstract : The catalytic activity of a heteropoly acid i.e. silicotungstic acid has been drastically improved along with the ease of recyclability and reusability. Silicotungstic acid has been heterogenized by coating STA over amine functionalized Si‐magnetite nanoparticles (STA‐Amine‐Si‐Magnetite) and the catalytic activity has been tested by the synthesis of 1 H ‐pyrazolo[1, 2‐ b ]phthalazinediones.